Legal and Ethical Aspects of Biotechnology Utilization for Public Health Improvement - Mubarak, Haikal; Miliyandra, Miliyandra; Priyanto, Eka; Respati, Gilang; Wiradirja, Imas Rosidawati (Formosa Journal of Applied Sciences, 2025)
Biotechnology has become an important tool in improving public health in many countries, including Indonesia. Ethical considerations such as social justice, experimental animal welfare, and individual privacy rights are some of the things that need to be considered in every step of biotechnology development. The impact of legal regulations and ethical considerations on biotechnology development cannot be ignored. This research aims to provide a comprehensive overview of the challenges and opportunities that exist in the utilization of biotechnology in Indonesia. Through case study analysis and statistical data, it is hoped that readers can understand the importance of the role of legal regulations and ethical considerations in optimizing the benefits of biotechnology for public health. This research methodology uses a qualitative approach with document analysis and case studies.